Matrix Remodeling Associated Genes (MXRAs): structural diversity, functional significance, and therapeutic potential in tumor microenvironments - Chao Zeng; Xiao Lv; Feng Wang; Yaomin Huang; Yanxian Ren; Hengwei Zhang (Discover Oncology)
Abstract The Matrix Remodeling Associated Genes (MXRAs) family, comprising eight distinct members (MXRA1-8), plays a crucial role in the development and maintenance of higher vertebrate cells. These proteins are primarily involved in the regulation of intercellular adhesion and the remodeling of the extracellular matrix (ECM). Recent investigations have highlighted the significant roles of MXRAs in the modulation of tumor growth and progression, establishing them as vital components in the oncogenic landscape. Notably, each MXRA member exhibits unique structural characteristics and functional properties, contributing to a diverse array of regulatory effects within the tumor context. This review seeks to provide a comprehensive analysis of the structural attributes, functional contributions, and activities of MXRAs within the tumor microenvironment. By elucidating the underlying mechanisms of action, this paper aims to offer novel insights and strategic approaches for the identification of early diagnostic biomarkers, as well as potential therapeutic targets that may facilitate molecular interventions aimed at inhibiting tumor development.